Shrinking the malaria map: Progress and prospects - Feachem, R; Phillips, A; Hwang, J; Cotter, C; Wielgosz, B; Greenwood, B; Sabot, O; Rodriguez, M; Abeyasinghe, R; Ghebreyesus, T; Snow, R (2010)
In the past 150 years, roughly half of the countries in the world eliminated malaria. Nowadays, there are 99 endemic countries - 67 are controlling malaria and 32 are pursuing an elimination strategy. This four-part Series presents evidence about the technical, operational, and financial dimensions of malaria elimination. The first paper in this Series reviews definitions of elimination and the state that precedes it: controlled low-endemic malaria. Feasibility assessments are described as a crucial step for a country transitioning from controlled low-endemic malaria to elimination. Characteristics of the 32 malaria-eliminating countries are presented, and contrasted with countries that pursued elimination in the past. Challenges and risks of elimination are presented, including Plasmodium vivax, resistance in the parasite and mosquito populations, and potential resurgence if investment and vigilance decrease. The benefits of elimination are outlined, specifically elimination as a regional and global public good. Priorities for the next decade are described. © 2010 Elsevier Ltd.